Change of sea ice content in the Arctic and the associated climatic effects: detection and simulation - I. I. Mokhov; V. A. Semenov; V. Ch. Khon; F. A. Pogarsky (Лëд и снег, 2015)
Modeling results of the impact of sea surface temperature and sea ice extent changes over the last decades on the formation of weather and climate anomalies are presented. It was found that the Arctic sea ice area reduction may lead to anti-cyclonic regimes’ formation causing anomalously cold winters in particular on the Russian territory. Using simulation with an atmospheric general circulation model, it is shown that the Early 20th Century Warming must have been accompanied by a large negative Arctic sea ice area anomaly in winter time. The results imply a considerable role of long-term natural climate variations in the modern sea ice area decrease. Estimates of the possible probability’s changes of the dangerous events of strong winds and high waves in the Arctic basin and favorable navigation conditions for the Northern Sea Route in the 21st century are made based on numerical model calculations. An increase of extreme wave height is found to the middle of the 21st century for Kara and Chukchi Seas as a consequence of prolonged run length and increased surface winds.